Application of Educational Media of Insulin Injection Rotation Scheme to Improve Insulin Injection Skills of T2DM Patients - Agustina Retno Hapsari; Iswanti Purwaningsih; Rohayati Masitoh; Isti Nuryani (Indonesian Journal of Global Health Research, 2024)
The number of Diabetes Mellitus patients is increasing and the average patient will use insulin injections independently to maintain their glycemic levels. Therefore, proper education is needed to improve insulin injection skills so that glycemic can be controlled. There are still many locations where insulin injections are carried out by patients and nurses in the arm (deltoid) or in the abdomen, but rotation is rarely carried out. This happens because it is to the patient's understanding and familiarity with the arm area. In general, patients say they are hesitant to inject insulin in the other part. Objective to determine the effect of the application of education using a rotation scheme on the skills of T2DM patients. This research method was with a quasi-experimental design, with the respondents being T2DM patients who received insulin injection therapy with a sampling technique using simple random sampling. With improved insulin injection skills, the patient can control his glycemic muscles. The results showed that there was an increase in the average skill score in the intervention group by applying educational media of the insulin injection rotation scheme higher than that of the control group. There was a significant difference (p-value 0.000). Education with the medium of insulin injection rotation scheme is effective in improving the skills of T2DM patients. Education using props will make it easier for T2DM patients to practice injecting independently precisely and correctly.